The Charters and Ordinances of the City of Richmond, with the Declaration of Rights, and Constitution of Virginia, at 227, An Ordinance Concerning Nuisances Other Than in the Streets, § 11 (1859) - (:unkn) unknown (General Publisher, 1859)
If any person shall sell, or expose for sale in this city, any torpedos, popcrackers, squibs, or other fire-works, of any kind whatever, except in packages containing each at least one hundred, or shall without permission in writing from the mayor, discharge, or set off, in any street or alley of the city, any balloon, rocket, torpedo, popcracker, fireworks or any combination of gunpowder, or any other combustible or dangerous material; or if any person shall, except under the fortieth section of the ordinance concerning streets, without necessity fire or discharge in this city any cannon, gun, pistol, or other fire-arms of any kind, or shall make therein any unusual noise, whereby the inhabitants thereof may be alarmed, or raise or fly a kite in this city, or if any auctioneer shall use any bell or herald to notify the public of any sale, except of real property, every such person herein offending, shall pay a fine of not less than one nor more than twenty dollars.
--
Keywords: DISCHARGE